2023
DOI: 10.1371/journal.ppat.1011015
|View full text |Cite
|
Sign up to set email alerts
|

An intact S-layer is advantageous to Clostridioides difficile within the host

Abstract: Clostridioides difficile is responsible for substantial morbidity and mortality in antibiotically-treated, hospitalised, elderly patients, in which toxin production correlates with diarrhoeal disease. While the function of these toxins has been studied in detail, the contribution of other factors, including the paracrystalline surface layer (S-layer), to disease is less well understood. Here, we highlight the essentiality of the S-layer in vivo by reporting the recovery of S-layer variants, following infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…However, in vitro and in vivo data showed that loss of slpA comes with a huge fitness cost. Indeed, slpA mutants produce less toxins, sporulate less, are more sensitive to antimicrobial peptides, and are avirulent ( 49 , 62 ). Therefore, phage resistance through receptor mutation would be compensated by loss of virulence, facilitating patient recovery.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vitro and in vivo data showed that loss of slpA comes with a huge fitness cost. Indeed, slpA mutants produce less toxins, sporulate less, are more sensitive to antimicrobial peptides, and are avirulent ( 49 , 62 ). Therefore, phage resistance through receptor mutation would be compensated by loss of virulence, facilitating patient recovery.…”
Section: Discussionmentioning
confidence: 99%
“…R20291 was rendered avirulent via deletion of the complete pathogenicity locus (encoding toxins A and B) using plasmid pJAK143 36 , yielding strain R20291Δ PaLoc . This strain was then further modified by deletion of DNA repair operon mutSL to create a hyper-mutator strain.…”
Section: Methodsmentioning
confidence: 99%